A Conceptual Approach to Economic Agglomerations - Madalina-Stefania Dirzu (CES Working Papers, 2012)
Technological progress and rapid structural adjustments have characterized a lot of economies in the last century and they still feature pronounced structures. An important observation is that economic activities tend to agglomerate in space as a result of some kind increasing returns, forming eventually economic agglomerations. When various companies gather together, they establish specific forms of interaction. Increasing returns produce when this mutual interplay creates positive externalities for those firms which operate into an agglomeration. In this context, it is crucial to raise a question: what is an economic agglomeration and what do different scientists imply when using the concept? The phenomenon of agglomeration has attracted researchers from various disciplines employing a hybrid set of analytical perspectives. This whole framework is still puzzled with contradictory conceptualizations which are often used in an ambiguous way. Scientists tend to utilize notions such as agglomeration, cluster, territorial network, specialization, concentration somewhat interchangeably and with little concern about how to operationalize them. To shed a light on this issue, the aim of this paper is to provide a comprehensive analyze of different theoretical framework in which economic agglomerations have been debated and researched.
Keywords: R10; R11; 330; economic agglomeration; cluster; territorial network; specialization; concentration Romania